Parallel shifts in differential gene expression reveal convergent miniaturization in fishes - Emily M. Troyer; William T. White; Ricardo Betancur-R; Dahiana Arcila (Proceedings of the National Academy of Sciences, 2025)
Body size variation in vertebrates is a complex polygenic trait, tightly correlated with numerous aspects of a species’ biology, ecology, and physiology. Miniaturization, the extreme reduction of adult body size, is a common phenomenon across the Tree of Life, yet the mechanisms underlying this process are poorly understood. Here, we investigate the molecular basis of body size evolution in goby fishes, a clade encompassing some of the smallest vertebrates on Earth. We generate a genome-wide phylogeny for 162 Gobioidei species and perform comparative transcriptomics across three clades with repeated instances of miniaturization and large-bodied forms. We identified 54 differentially expressed one-to-one orthologs between miniature and large-bodied species. These genes reveal distinct functional profiles, suggesting that regulation of cell numbers is a key mechanism governing body size control. Miniature species consistently overexpress growth inhibitors like CDKN1B and ING2 , associated with tighter cell cycle regulation and decreased proliferation rates, while large-bodied species upregulate growth-promoting genes such as TGFB3 , linked to tissue development and growth signaling. These enriched functional pathways, conserved since the Eocene (50 Ma), suggest macroevolutionary convergence in size regulation over deep time. Our findings provide insights into how size determination is governed at a genetic level and highlights the importance of exploring these factors in nonmodel organisms to uncover the fundamental processes regulating vertebrate body size evolution.